The Internet as a transnational project: connecting Central America through computer networks (1990–1996) - Siles González, Ignacio (2018)
This article argues that transnational flows of knowledge, data, and technologies are not only an actual feature of the Internet, but rather a constitutive characteristic of its historical development. To make this case, it discusses how six countries in Central America-Costa Rica, El Salvador, Guatemala, Honduras, Nicaragua, and Panama-connected to and through computer networks and technologies such as UUCP, BITNET, and the Internet in the first half of the 1990s. Drawing on archival research and interviews with protagonists of networking initiatives, this article argues that the establishment of these projects in Central America required forging a transnational network of collaborations, enabled by international organisations with presence in countries of the region. This study reveals how the Internet was imagined and enacted in a part of the world largely absent in academic literature. It thus broadens our understanding of the early development of computer networks in the global South.